“Which Factors Affect Pregnancy Until Calving and Pregnancy Loss in Buffalo Recipients of in vitro Produced Embryos?” - Saliba, Wilson Pardini; Gimenes, Lindsay Unno; Drumond, Roberti Martins; Bayão, Henrique Xavier Salgado; Di Palo, Rossella; Gasparrini, Bianca; Rubessa, Marcello; Baruselli, Pietro Sampaio; Sales, José Nélio Souza; Bastianetto, Eduardo; Leite, Rômulo Cerqueira; Alvim, Mucio Túlio Teixeira (Frontiers in Veterinary Science, 2020)
In vitro embryo production and embryo transfer (ET) in buffaloes has been developed for decades. However, most studies are focused on the donor or laboratory improvements and there is a lack of reports regarding the recipients. Therefore, our aim was to investigate factors associated to pregnancy (P/ET), pregnancy loss (PL), and calving rates in buffalo recipients. The studied factors were season, recipient parity, synchronization protocol, CL diameter, asynchrony between embryo and recipient, day of recipient estrous cycle, embryo (fresh vs. vitrified), day of embryo development, and embryo stage. These retrospective data, from a program of in vitro produced embryos, were analyzed by logistic regression and odds ratio was also estimated. Two factors were related to P/ET and calving rate: 1) progesterone associated to estradiol plus eCG protocol for fixed time ET tended to affect positively P/ET on day 30 (41.9% vs. 36.1%, respectively; P = 0.07; AOR = 1.28) and P/ET on day 60 (37.8% vs. 36.1%, respectively; P = 0.09; AOR = 1.08) compared to Ovsynch protocol; 2) CL diameter (≥ 14.5 mm) at transfer increased P/ET on day 30 (47.4% vs. 32.5%; P < 0.01; AOR = 1.87), on day 60 (45.3% vs. 27.7%; P < 0.01; AOR = 2.16), and also calving rate (37.9% vs. 21.7%; P < 0.01; AOR = 2.20). PL was greater when ET was done in the nonbreeding season compared to the breeding season (PL 30-60: 12.8% vs. 0.0%, P = 0.01; AOR > 999.99; PL 60-calving: 26.8% vs. 3.6%, P = 0.03; AOR = 9.90; and PL 30-calving: 36.2% vs. 3.6%, P = 0.01; AOR = 15.30). In conclusion, data of our study indicated that synchronization protocol, CL diameter and ET during the breeding season impacted the reproductive efficiency of buffalo recipients.